Frequency of Dental Caries in Undergraduate Dental Students - Amna Bilal, Namrah Bashir, Fasila Rashid, Rashid Hassan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of dental caries in undergraduate dental students. Study design: Cross-sectional study Place and duration of study: Ayub Medical College, Abbottabad from 1st March 2022 to 31stAugust 2022. Methodology:One hundred and forty students of dental with ages 17-25 years were enrolled. Detailed demographics were recorded after informed written consent. More than 25 years age students and reluctant students were excluded.Procedure recommended by WHO was followed to document the oral health status for dental caries. Results: There were 63(45%) males and 77(55%) females. Maximum of the students 37(26.4%) and 36(25.7%) belong to the age group 19-21 and 21-23 respectively. Seventy nine (56.3%) were the residents of urban area while 23(16.42%), 39(27.85%), 32(22.85%) and 46(32.85%) students were taken from 1st, 2nd, 3rd and 4th year respectively. Out of all the pupils, 103(73.57%) had dental caries with a DMFT score (>0), whereas 37(26.43%) were healthy. Conclusion: Compared to men, women are more likely to progress dental caries. The average total DMFT score differential did not affect either party much. DMFT score and age cluster associations were very statistically significant. The average DMFT score for females across the different academic levels did not differ significantly. While other DMFT score elements were non-significant, the decaying factor of the average DMFT score dramatically reduced. Keywords: Dental Caries, DMFT Index, World Health Organization (WHO)